Pattern and Risk Factors of Diabetic Retinopathy among Type 2 Diabetic Patients: Experience in a Tertiary Care Hospital (Journal of Medicine, 2016)
Background: Diabetic retinopathy is the commonest cause of blindness in the working age group of both developed and developing countries. It is the indicator of all micro-vascular complications of diabetes mellitus. This study was aimed to find out the frequency and pattern of diabetic retinopathy among hospitalized adult type 2 diabetic patients.Methodology: This cross-sectional study was carried out in the Department of Medicine and Endocrinology of BIRDEM General Hospital, Dhaka over a period of six months. Retinopathy was determined by fundoscopic examination in dilated pupil. Data were collected in preformed questionnaire including demographic characteristics, fundoscopic findings, and laboratory investigation reports with prior informed consent of the patients.Results: Total patients were 94, male were 52 and female were 42. Mean age of the patients was 52.2 ± 11.12 years. Hypertension was the most common (42.8%) co-morbid condition followed by dyslipidemia (33%), nephropathy (34%), neuropathy (21.3%), ischemic heart disease (9.6%) and stroke (5.3%). Study showed 37.23% Patient had good glycemic control (HbA1C